Perlindungan Konsumen Terhadap Wanprestasi dalam Investasi Perdagangan Pada Aplikasi Jombingo Buy-Together - Sari, Puput Novita; Berlianty, Teng; Kuahaty, Sarah Selfina (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Investment can be defined as the process of placing a certain amount of funds in a particular asset with the hope of obtaining profits from that capital in the future. Investment in the Jombingo Buy-Together application itself takes the form of investing capital by purchasing goods in the application and then getting a number of profits from purchasing goods. The legal basis governing capital investment is regulated in Law Number 25 of 2007 concerning Capital Investment. The research method used is normative juridical, using a statutory approach and a conceptual approach, the legal materials used are primary, secondary and tertiary. Collecting legal materials using literature study, and then analyzing them using qualitative analysis techniques. The results of this research show that legal protection for consumers who suffer losses in trading investments on the Jombingo buy-together application is divided into 2, namely preventive protection and repressive protection. Preventatively, namely legal protection aims to prevent losses or problems experienced by buyers. Several forms of preventive legal protection for consumers which regulate consumer losses in investments, as well as the rights and obligations of the parties, namely Law Number 8 of 1999 concerning Consumer Protection, Law Number 21 of 2011 concerning the Financial Services Authority, Law Number 19 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, and Financial Services Authority Regulation Number 6/Pojk.07/2022 concerning Consumer and Public Protection in the Financial Services Sector. Meanwhile, repressively, namely in the form of dispute resolution. Article 45 of the Consumer Protection Law states that every buyer who experiences a loss can resolve the dispute through litigation or non-litigation, based on the voluntary choice of the parties to the dispute.